Improved visual acuity after microsurgical clipping of a symptomatic anterior cerebral artery aneurysm: case report - Arcan, Fatih; Unterberg, Andreas; Zweckberger, Klaus (British journal of neurosurgery, 2019)
BACKGROUND: Symptomatic aneurysms of the anterior cerebral artery causing visual impairments are rare and preponderantly lacking in the literature. It is further under discussion, whether operative clipping or endovascular coiling might be superior in order to achieve visual recovery. We therefore present a case of a patient with progressive visual loss caused by an aneurysm of the right A1-A2 segment compressing the ipsilateral optic nerve. METHODS: A 57-year-old woman was admitted to our neurosurgical department with visual impairment of the right eye. On admission, visual acuity was 0.05 dpt. and visual field testings showed severe medial and lateral quadrant-anopia. MRI scans and angiography (DSA) demonstrated an aneurysm of the A1-A2 segment compressing the right optic nerve. During surgery, the aneurysm was clipped, the space-occupying dome removed and the nerve relieved from any adhesions. Instantaneously after surgery, visual acuity significantly improved from 0.05 to 0.9 dpt. CONCLUSIONS: Anterior cerebral artery aneurysms may present with acute visual impairments and surgical clipping significantly improves impaired visual acuity. 5520 |s|Symptomatic intracranial aneurysm; anterior cerebral artery aneurysms; clipping; visual acuity; optic nerve compression